Binding sites of E. coli and B. stearothermophilus ribosomal proteins on B stearothermophilus 5S RNA. - Zimmermann, J (1978)
The primary binding sites for Bacillus stearothermophilus proteins B-L5 and B-L22 and the Escherichia coli proteins E-L5, E-L18 and E-L25 on B. stearothermophilus 5S RNA were determined by limited ribonuclease digestion of the corresponding 5S RNA-protein complexes. The results obtained in this study are in agreement with our previous experiments in which the binding sites of E. coli and B. stearothermophilus proteins were determined for E. coli 5S RNA and lead to the conclusion that the proteins interact with the most conserved regions of 5S RNA. A comparison of the results obtained in this study with those of other published experiments suggest that the proposed interaction of nucleotides 16-21 with those of 58-63 is facilitated by protein binding to 5S RNA.